Dampak Brand Positioning Terhadap Persepsi Konsumen Dan Niat Membeli di Toko Kijora Lemang Batok - Christian Putra Tarigan; Jois Simarmata; Lidia Mutiara Hutasoit; Lenti Susana Saragih (Universitas Kristen Indonesia Toraja, 2024)
This research aims to evaluate the impact of brand positioning strategies on consumer perceptions and purchase intentions in the Lemang Batok store context. The Lemang Batok store is considered as a research object to understand how brand positioning can influence consumer perceptions and their desire to purchase this unique product. Mixed methods were used to combine survey and interview data to gain a holistic understanding.